Learning Objectives in Lesson Plans based on Kurikulum Merdeka Designed by PPG Students of Bengkulu University - Ronel, Dido; Puspita, Hilda; Mulyadi, Mulyadi (UNIB Press, 2025)
This study analyzes the quality of learning objectives in lesson plans based on the Kurikulum Merdeka, as designed by students in the English Teacher Professional Education Program (PPG) at the University of Bengkulu. Employing an explanatory sequential mixed methods design, the research involves the quantitative analysis of 25 lesson plans comprising a total of 65 learning objectives created by pre-service English teachers. The quantitative phase uses a 10-item evaluative checklist to assess the quality of each objective in terms of clarity, measurability, and alignment with the core principles of Kurikulum Merdeka, including student-centeredness, competency orientation, and differentiated instruction. Following this, qualitative data were gathered through semi-structured interviews with three randomly selected participants to gain deeper insights into the challenges encountered during the formulation of learning objectives. Findings reveal that, overall, the learning objectives are of good quality, with a majority reflecting satisfactory alignment with curriculum demands. However, some challenges persist, such as inadequate skills in conducting needs analysis, difficulty in translating learning outcomes into specific and measurable objectives, and limited access to supporting materials and references. The study highlights the need for more structured training in curriculum implementation and concludes with suggestions for future research exploring effective strategies and models for developing high-quality learning objectives within the context of Kurikulum Merdeka.